Assessment of DEM generated by UAV photogrammetry for volume calculation / Firdaus Abd Rashid - Abd Rashid, Firdaus (2022)
Volume calculation are apart of measurement of engineering survey where it needed to know the total materials available and to manage quantities. To calculate volume precisely and accurate, ground survey need to be done by surveyors which is also take more cost, man power, and also time taken to calculate volume of material available. The most effective technique for volume calculation again large amount of stockpile is photogrammetry. The aim of this study is to test the capability of unmanned aerial vehicle (UAV) in volumes measurement. The main software that will be use in this study is Agisoft Metashape and Global Mapper. Method used in this research is compare the result of volume between UAV and total station survey. The result is comparing RMSE, area, volume, and surface of the DEM generated by both method. Base on the result, the different of UAV and total station survey is 2.951%. Importance of this study is surveyor will be more confident to make volume measurement using UAV in future project.